POLITENESS PRINCIPLES:THEIR REALISATION IN INDONESIAN APOLOGIES - Wuryani Hartono (Soegijapranata Catholic University, 2002)
The politeness principles in the realm of pragmatics are know to be universal. Yet, to what degree the iniversity of such principles applies to a particular language is worth revealing. This study has a two-folded purpose, i.e. to look at the realisation of the politeness principles in Indonesian apologies and to demonstrate the patterns of this particular speech act according to the CCSARP coding scheme as proposed by Blum Kulka & Olshtain (1998).